Species structure of the bird communities of the middle Uzh river flow in Zakarpattia province of Ukraine in the nesting period - Stankiewicz-Volosianchuk, Oksana (ScienceRise: Biological Science, 2020)
The article analyzes characteristics of the species structure of the bird communities in the middle Uzh river valley in the breeding period by the ratio of the number of species and their abundance, the shares of dominant, background and rare species, the types of nesting and feeding, landscape and ornitho-geographic aspects. The main factors for the formation of the species diversity and the peculiarities of the species structure of bird communities have been identified. The goal of the study was to investigate and analyze the species structure of bird communities to determine the intensity of the urbanization impact onto the natural ecosystems in this segment of the Uzh valley. Material and Methods. Data were collected during the 2016-2018 years during nesting periods. The bird censuses were conducted by the route method, followed by processing of the collected data. Results and discussion. Within the study period, 71 bird species have been identified here. The bird population density is 839.64 ind./km2. Birds of forest landscapes (47.9%) are dominant. Tree-nesting (in crowns, hollows, and shrubs) birds composed in total 60.6%. The share of zoophagous birds is 57.7%. By the fauna type, trans-Palearctic species are dominant: 42.3%. By the fauna type, transpalearctic species are dominant (42.3). The urbanization of the Uzh valley is evidenced by the presence of a group of synanthropic bird species, which are inseparably linked to rural settlements, located along the river (share of all species - 12.7%, share of total bird population - 17.15%). Conclusions. The species structure of birds communities during the nesting season in the middle Uzh river flow evidences that the impact of urbanization on natural ecosystems of the river valley is low despite the close location of villages